Constant gradient elastography with optimal control RF pulses - Van Reeth, Eric; Lefebvre, Pauline M.; Ratiney, Hélène; Lambert, Simon A.; Tesch, Michael; Brusseau, Elisabeth; Grenier, Denis; Beuf, Olivier; Glaser, Steffen J.; Sugny, Dominique; Tse-Ve-Koon, Kevin (Journal of magnetic resonance (1997), 2018)
[Display omitted] •Specifically designed radio-frequency pulses are used to perform motion encoding.•Magnetic Resonance Elastography is performed with only a constant gradient.•An analytic development is provided to detail the motion encoding mechanism.•Superior phase-to-noise ratio is obtained compared to standard encoding methods. This article presents a new motion encoding strategy to perform magnetic resonance elastography (MRE). Instead of using standard motion encoding gradients, a tailored RF pulse is designed to simultaneously perform selective excitation and motion encoding in presence of a constant gradient. The RF pulse is designed with a numerical optimal control algorithm, in order to obtain a magnetization phase distribution that depends on the displacement characteristics inside each voxel. As a consequence, no post-excitation encoding gradients are required. This offers numerous advantages, such as reducing eddy current artifacts, and relaxing the constraint on the gradients maximum switch rate. It also allows to perform MRE with ultra-short TE acquisition schemes, which limits T2 decay and optimizes signal-to-noise ratio. The pulse design strategy is developed and analytically analyzed to clarify the encoding mechanism. Finally, simulations, phantom and ex vivo experiments show that phase-to-noise ratios are improved when compared to standard MRE encoding strategies.